Changes in job strain in relation to changes in physiological state. A longitudinal study. - Theorell, Töres; Perski, Aleksander; Åkerstedt, Torbjörn; Sigala, F.; Ahlberg-Hulten, G.; Svensson, J.; Eneroth, P. (Scandinavian Journal of Work, Environment & Health, 1988)
A sample of 73 men and women aged 22-63 years and working in six different occupations (air traffic controllers, waiters, physicians, symphony orchestra musicians, baggage handlers, and airplane mechanics) participated in a longitudinal study four times during a year. The spontaneous variations in job strain (determined as the self-reported ratio between psychological demands and decision latitude) were substantial. The average difference between the occasion with the highest level of strain and the occasion with the lowest level was 25% of the total mean. Systolic blood pressure during workhours, as well as self-reported sleep disturbance, increased when demands increased in relation to decision latitude. Among men with a depressive tendency (according to a diary) morning plasma prolactin levels increased markedly with increasing job strain. Among subjects with a positive family history of hypertension the increase in systolic blood pressure at work was particularly pronounced, and among the men in this group a lower than expected level of morning cortisol was found measured during the period with the highest level of strain.